Problematizing the Relationship between Rural Small Schools and Communities: Implications for Youth Lives - Cuervo, Hernán (Alberta Journal of Educational Research, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-AU X-NONE X-NONE <![endif]–> Small schools are often the hub of many rural communities. In the school space, a multiplicity of social, economic and political relationships are sustained, which enhance the vitality of the community. As such, the relationship between small schools and communities is often presented as a powerful one; however, too often as a harmonious, natural and simple construction. This paper article argues that when education, youth and communities are defined through apparently simple, universal, natural and neutral conceptualizations, these are commonly based on prescribed norms that reflect the dominant values of an hegemonic majority. These homogeneous and universal conceptualizations of education, youth and community serve to legitimize processes of inequality and marginalization, and to undermine the goals these aim to contribute to. This article draws from disciplines such sociology of youth, education, rural studies and political theory to problematize the relationship between small schools and communities in rural spaces by analyzing the intersection of education and youth policies, as constructed by neoliberal policies, and the idea of community as presented by communitarians. It argues for the need to rethink the relationship between small schools and communities towards a more plural and socially just one that overcomes processes of exclusion and marginalization. Les petites écoles sont souvent au centre des communautés rurales. Une multiplicité de rapports sociaux, économiques et politiques se maintiennent à l’école, ce qui augmente la vitalité de la communauté. Le rapport entre les petites écoles et les communautés est ainsi souvent présenté comme un lien puissant; toutefois, il est trop souvent dépeint comme une construction harmonieuse, naturelle et simple. Cet article soutient que lorsque l’éducation, les jeunes et les communautés sont définis par des conceptualisations apparemment simples, universelles, naturelles et neutres, celles-ci sont généralement fondées sur des normes qui reflètent les valeurs dominantes d’une majorité hégémonique. Ces conceptualisations homogènes et universelles de l’éducation, les jeunes et les communautés viennent légitimer les processus d’inégalité et de marginalisation, et compromettent les objectifs auxquels ils voudraient contribuer. Cet article puise dans des disciplines comme la sociologie des jeunes, l’éducation, les études rurales et la théorie politique pour problématiser le rapport entre les petites écoles et les communautés dans les milieux ruraux et ce, en analysant d’une part, l’intersection de l’éducation et les politiques touchant les jeunes, telles qu’élaborées par les politiques néolibérales, et d’autre part, l’idée de communauté comme elle est présentée par les partisans du mouvement communautaire. L’article met de l’avant le besoin de repenser le rapport entre les petites écoles et les communautés de sorte à arriver à une vision davantage pluraliste et socialement équitable qui surmonte les processus d’exclusion et de marginalisation. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>